Should you tell patients about beneficial treatments that they cannot have? No. Issue 7598 (19th April 2007) - Firth, John
Abstract : No healthcare system can afford to pay for all available treatments. Robert Marcus believes doctors have a duty to tell patients about unfunded drugs, but John Firth argues that it will cause them harm